The skeptical professional's guide to psychiatry : on the risks and benefits of antipsychotics, antidepressants, psychiatric diagnoses, and neuromania - Dean, Charles E. (New York, NY : Routledge, 2021)
"This text critically examines the shortcomings of psychiatry, the flawed development of the diagnostic system, including the DSM-5, and the failure to advance the effectiveness of antipsychotics and antidepressants. Starting with an overview of the evolution of psychiatry, Dean explores the creation, use, and misuse of medications, a process largely driven by the drug companies. Other chapters describe the benefits and risks of medications, the problems associated with rational prescribing, and the embrace of so-called novel therapies including hallucinogenic drugs and opioids. Chapters end with a set of clinical notes that provide specific recommendations to clinicians, families, patients, and other providers, emphasizing the risks and benefits of treatment with medications, but also stressing alternative approaches. This book will challenge clinicians to think critically about the DSM-5 and the current systems of diagnosis and treatment of mental illnesses in the hopes of ultimately improving the lives of people with mental illnesses"--
The Biological Revolution in Psychiatry : An Overview of the Dark Ages -- The Biological Revolution : The Middle Years and the Rise of Psychopharmacology -- Has the Biological Revolution Delivered? A Focus on Antipsychotics -- Antipsychotics and the Metabolic Syndrome, Cardiovascular Disease, and Mortality -- Antipsychotics and Mortality in the Elderly with Dementia -- Psychotropic and Antipsychotic Polypharmacy : Common Practice, Good Medicine? -- The Neurologic Consequences of Antipsychotics : From Parkinsonism to Tardive Dyskinesia -- Antidepressants and Depression: Background and Biology -- Antidepressants : Do They Work? If So, When, How Often, and at What Costs? -- Antidepressants and Adverse Events : Falls and Fractures, Vascular Events, Risks in Pregnancy, and Abnormal Movements -- Treatment-Resistant Depression : Combining and Switching Antidepressants, Adding Antipsychotics, and On to Neurotherapeutics -- Desperately Treating Depression : On Psychotogenic and Hallucinogenic Drugs, Anti-Inflammatories, Antidiabetics, Hyperthermia, and Opioids -- Psychiatric Diagnoses : The DSM and the Roots of Failure -- Fear and Loathing at the APA : The DSM-5, The Brain Mapping Quartet, and the Future of Mental Illness.
OCLC-licensed vendor bibliographic record.
Keywords: Psychopharmacology; Mental illness -- Chemotherapy -- Evaluation; Psychiatry -- History; MEDICAL / Psychiatry / Psychopharmacology; PSYCHOLOGY / Clinical Psychology